2016
DOI: 10.15825/1995-1191-2016-2-99-109
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Remodeling of Biodegradable Small-Diameter Vascular Grafts in Situ

Abstract: Aim: to evaluate the biomechanical remodeling of polymer grafts modified with vascular endothelial growth factor (VEGF) after implantation into rat abdominal aorta.Materials and methods. Vascular grafts of2 mmdiameter were fabricated by electrospinning from polycaprolactone (PCL) and a mixture of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) and PCL. The grafts were modified with VEGF by biphasic electrospinning. Morphology of the grafts was assessed by scanning electron microscopy. Physico-mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…In addition, the sections of the PHBV/ PCL/VEGF, PHBV/PCL/bFGF, and PHBV/PCL/SDF1a grafts with the diameter of 2 mm, which long-term patency has been reported previously in [3,5], and the sections of the non-woven PHBV/PCL/VEGF, PHBV/ PCL/bFGF, PHBV/PCL/SDF-1a matrices, the respond to their subcutaneous implantation has been studied in [6], underwent the similar staining procedure for the assessment. They were then immersed in a 2% aqueous solution of alizarin red C for 70 seconds, then nuclei of cells were stained with DAPI 10 μg/ml for 3 minutes.…”
Section: Calcification Assessmentmentioning
confidence: 56%
“…In addition, the sections of the PHBV/ PCL/VEGF, PHBV/PCL/bFGF, and PHBV/PCL/SDF1a grafts with the diameter of 2 mm, which long-term patency has been reported previously in [3,5], and the sections of the non-woven PHBV/PCL/VEGF, PHBV/ PCL/bFGF, PHBV/PCL/SDF-1a matrices, the respond to their subcutaneous implantation has been studied in [6], underwent the similar staining procedure for the assessment. They were then immersed in a 2% aqueous solution of alizarin red C for 70 seconds, then nuclei of cells were stained with DAPI 10 μg/ml for 3 minutes.…”
Section: Calcification Assessmentmentioning
confidence: 56%
“…Previously, we showed that PHBV/PCL vascular grafts are populated by ECM-producing cells within 6 months following implantation, which results in a decrease in their relative elongation and Young’s modulus. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Так, ранее мы показали изменение механических свойств пористого биодеградируемого материала в соответствии со свойствами нативных тканей после 6 мес. имплантации in vivo [27].…”
Section: Discussionunclassified